2011
DOI: 10.1084/jem.20100370
|View full text |Cite
|
Sign up to set email alerts
|

Growth differentiation factor 15 deficiency protects against atherosclerosis by attenuating CCR2-mediated macrophage chemotaxis

Abstract: The TGF-β family member GDF-15 promotes lesion formation and plaque instability in atherosclerosis-prone LDLr-deficient mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
145
4
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 174 publications
(159 citation statements)
references
References 30 publications
5
145
4
5
Order By: Relevance
“…These mediators contribute to a local inflammatory environment, which further activates resident fibroblasts, leading to a chronic wound-healing process and ultimately fibrosis (4). Indeed, it was previously demonstrated that GDF-15 acts as a macrophage recruitment signal through the CCR2/CCL2 axis (12). GDF-15 may thus be involved in immune recruitment to the lung at given stages by stimulating the release of mediators such as IL-6 and CCL2.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These mediators contribute to a local inflammatory environment, which further activates resident fibroblasts, leading to a chronic wound-healing process and ultimately fibrosis (4). Indeed, it was previously demonstrated that GDF-15 acts as a macrophage recruitment signal through the CCR2/CCL2 axis (12). GDF-15 may thus be involved in immune recruitment to the lung at given stages by stimulating the release of mediators such as IL-6 and CCL2.…”
mentioning
confidence: 99%
“…From this perspective, elevated GDF-15 levels are considered an endogenous protective mechanism for limiting cardiovascular damage (11). GDF-15 expression is also involved in inflammation, as substantiated by its involvement in CCR2-mediated chemotaxis (12).…”
mentioning
confidence: 99%
“…Because extended upregulation of NAG-1 can be involved in the progress of human IBD, more careful evaluations of extended NAG-1 actions should be performed in the context of chronic inflammatory responses in IBD patients. For instance, increased NAG-1 expression can increase MCP-1 and its receptor expression in macrophages in a TGF-bRII-mediated pathway and promotes macrophage chemotaxis during chronic inflammation (18). Our recent investigations suggested also that NAG-1 can enhance the production of proinflammatory cytokines via activation of NF-kB, a central proinflammatory transcription factor, in the mucosal infection models (21,36).…”
Section: Discussionmentioning
confidence: 92%
“…Although NAG-1 is involved in acute stress-induced apoptotic process (10), increasing recent evidences demonstrated that NAG-1 can trigger homeostatic cellular responses and play protective roles in both physiological and pathological states, including chronic inflammation and tumorigenesis (16)(17)(18)(19). In response to the cytotoxic NSAIDs, cells also can produce the survival signals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation